Effectiveness of Black Honey as an Antiinflammatory Substance in Rat’s Wound Infected by Staphylococcus aureus - Fanny Gunawan; Willy Sandhika; Nurul Wiqoyah (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Black honey contains higher flavonoids, phenols, and minerals, which serves as antiinflammatory agents and promote faster wound healing. Purpose: This study aimed to determine the effectiveness of black honey on macrophage cells and blood vessels in rats’ wounds infected with Staphylococcus aureus. Methods: This was an experimental study with a post-test only control group design. This study involved 24 rats divided into 4 groups. The treatment was carried out for 5 days. The rats in the K1 group were wounded (cut) and given aquadest. The rats in the K2 group were wounded (cut), infected with Staphylococcus aureus, and given aquadest. The rats in the P1 group were wounded (cut), infected with Staphylococcus aureus, and treated with 2ml of black honey topically. The rats in the P2 group were wounded (cut), infected with Staphylococcus aureus, and treated with2ml of black honey orally. Observations were made histopathologicaly using hematoxylin-eosin (HE) staining by calculating the number of macrophage and blood vessels, and further using One-Way ANOVA. Result: The number of macrophages and blood vessels between groups was significantly different. The K2 group had the highest mean number of macrophage cells and blood vessels, and the K1 group was the least. The mean number of macrophage cells in the P1 group was more than the K1 group and less than the K2 and P2 groups, both significantly. Conclusion: Black honey was effective in reducing inflammation in wounds infected by Staphylococcus aureus.